Voltage sag detection technique based on phase angle analysis for PWM-Switched autotransformer - Mansor M. (Praise Worthy Prize S.r.l, 2023)
Voltage sag can cause expensive downtime, making it the focus of considerable research. Many voltage sag detection techniques have been introduced to measure and to detect voltage sags, such as RMS Value Evaluation and Peak Value Evaluation techniques. Most of them require a delay for sag to be detected and compensated, whereas immediate sag detection is vital to improvement of transient performance. This paper presents a new voltage-sag detection technique that is based on phase-angle analysis, capable to detect and to compensate sag the moment it occurs. Its effectiveness and capability had been verified through a MATLAB/Simulink simulation. A study on existing techniques, i.e., RMS Value Evaluation and Peak Value Evaluation, is included as comparison with the proposed technique. 2010 Praise Worthy Prize S.r.l. - All rights reserved.